Transient Thermal Model of Airflow Effects in Human Eye Temperature - K.C., Gokul; Gurung, D.B.; Adhikary, P.R. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
High air speed makes thinner the thermal boundary layer between cornea and environment. This accelerates evaporation of water and convective heat transfer. Both factors drop corneal temperature. Most of the literatures of thermal modeling in human eye air forced convection effects is not considered. Based on different climatic conditions of Nepal and their impact on two-wheeler rider’s eye, one dimensional variational finite element model is developed to investigate the forced convection effects of airflow in eye temperature distribution. The bio-heat transfer process is simulated in transient state cases. The results show that, high air speed decreases corneal temperature rapidly in cold climate but there is no significant decrease found in hot climate. The corneal temperature starts to plateau from approximately same time at same air speed and in different ambient temperature.